Green fabrication of tinospora cordifolia-derived MgO nanoparticles: Potential for diabatic control and oxidant protection - B.V. Vamsi Krishna; P. Tirupathi Rao; B. Durga Lakshmi; K. Vasudha; Sk. Esub Basha; B. Putra Kumar; PS S.Sai Kiran; K. Shreyas Chandra; Ramachandra R.K (Next Materials, 2024)
Pure and encapsulated magnesium oxide (MgO) nanoparticles were synthesized using a hydrothermal method with Tinospora Cordifolia (TC) leaf extract. XRD analysis revealed a face-centered cubic structure for both types of nanoparticles, with an average crystallite size of 26.94 nm and 36.48 nm. The pure and encapsulated MgO nanoparticles were confirmed by UV-Visible spectrophotometer, the encapsulated MgO nanoparticles had a lower optical energy band gap of 5.304 eV compared to pure MgO nanoparticles at 5.506 eV. FTIR and BET results confirmed the presence of phytochemicals such as phenolic and flavonoid groups encapsulated over the surface of MgO nanoparticles. HRTEM analysis showed nearly spherical shaped encapsulated MgO nanoparticles with a thickness of 8.1 nm. Histogram represents the average particle size of encapsulated MgO NPs was found to be 37.08 ± 4.70 nm. In vitro analysis revealed that these nanoparticles exhibited anti-diabetic and anti-oxidant properties that were comparable to commercially available Metformin drug. The antidiabetic and antioxidant ability of encapsulated MgO NPs was shown by effective inhibition against carbohydrate digestive enzymes such as α- amylase and α-glucosidase with IC50 values of 48.71 µg/ml and 46.29 µg/ml respectively and DPPH radical with IC50 value of 48.012 µg/ml. Encapsulated MgO nanoparticles exhibited higher efficacy in vitro against carbohydrate digestive enzymes and DPPH free radicals than pure MgO nanoparticles due to the presence of phenolic and flavonoid groups. The spectral analysis indicates that the use of Tinospora Cordifolia extract to synthesize MgO nanoparticles results in a green method that shows promise for various biomedical applications.